Competitividade regional em municípios brasileiros: uma proposta metodológica de classificação e análise baseada na Design Science - Dresch, Leonardo de Oliveira (2021)
Understanding the reasons that lead regions to develop in different ways and at different rates represents a major challenge for policy makers and academics. The problem that this thesis sought to address was: how can the regional competitiveness of Brazilian municipalities be studied and understood in a viable and operational way? Regional competitiveness is a concept that has remained on the agenda since the 1990s and presents itself with a theoretical and empirical option. The territorial capital approach, in complementarity, also seeks to explain the competitive elements through the offer centered on territorial assets (endogenous factors). The World Economic Forum, European Commission and many other organizations continue to make efforts to understand, classify and analyze competitiveness in different space units (countries, states, municipalities and regions). Measuring regional competitiveness and understanding its dynamics represent challenges that, if overcome, can help to create a robust territorial development plan. The objective of this work is to propose a dynamic method of classification and analysis of regional competitiveness in Brazilian municipalities. Specifically, i) to identify and describe the variables that affect regional competitiveness in Brazilian municipalities; ii) propose a dynamic and applied method for the classification and analysis of regional competitiveness in Brazilian municipalities; and, iii) empirically test the proposed method to analyze regional competitiveness in municipalities in the state of Mato Grosso do Sul, one of the centers of agribusiness in Brazil. The answers were sought through Design Science Research, a pragmatic methodology, as well as assumptions from the New Economic Geography (NGE) and New Urban and Neoclassical Economics (NEUN). The perception of experts and policy makers was used, together with the framework of Data Science and Spatial Analysis techniques, in order to design relevant tools for the community of interest and capable of offering satisfactory solutions considering the costs and benefits. The results led to the development of artifact 1, Map of Variables of Municipal Regional Competitiveness, and artifact 2, Dynamic method of classification and analysis of regional competitiveness in Brazilian municipalities. In the first artifact, a method and two data collection instruments were developed, IC-01 and IC-02, whose empirical test resulted in a model with three groups, eleven subgroups and fifty-two explanatory variables for regional competitiveness. The second artifact accounted for a collection method and instrument, IC-03, whose operationalization for evaluation in Mato Grosso do Sul generated six different techniques for measurement / classification, including a ranking and a model with classification potential congruent with the experts' perception by 74.68%. The most relevant explanatory variables for the classification of Regional Competitiveness, according to experts, were the Gross Domestic Product (GDP) and the diversity of business activities available in the municipalities. ICRM, on the other hand, considered the density of access to landlines, poverty and the dependency ratio as the most relevant. The municipalities with the highest QLs related to agriculture and the public service showed lower regional competitiveness. Spatially significant relationships were also identified between homicide rate, poverty and extreme poverty, dependency ratio, people per household and inadequate water and sewage supply with low regional competitiveness. The work, therefore, presented operational methods and techniques to study and understand the municipal regional competitiveness, identifying and describing explanatory variables, proposing a measurement and classification method and demonstrating analysis techniques in the empirical test carried out in the municipalities of Mato Grosso do Sul. Regional competitiveness allows policy makers to direct resources and efforts to overcome inequalities between municipalities and consequently generate the diffusion of regional development potential.